Agronomic evaluation of different lettuce (Lactuca sativa L.) varieties under unheated plastic tunnel - Kovácsné Madar, Á.; Takácsné Hájos, M. (International Journal of Horticultural Science, 2022)
Among the leafy vegetables, lettuce (Lactuca sativa L.) is the most widely grown species in the world. Wide ranges of physical properties of the products are used to assess the degree of maturity. In this study, different lettuce varieties were grown under an unheated plastic tunnel in springtime. We evaluated the agronomic properties of different lettuce varieties, evaluated the condition of the plants, and determined the bioactive substances. Larger head weight can be achieved by the ‘King of May’ butterhead (259.31 g) and ‘Great Lakes 659’crisphead (220.40 g) genotypes. A very strong correlation (r = 0.995) was observed between the lettuce head index, and leaf index and both had a strong positive correlation (r = 0.828 and 0.760) with NDVI. The highest SPAD values were measured for cos lettuce ‘Romaine lettuce’ (44.01) and iceberg lettuce ‘Great Lakes 659’ (42.71). However, these genotypes showed the highest (9.52%; 8.74%) dry matter content, too. The red leaf variety 'Lollo Rosso' had the highest total polyphenol content (181.53 GAE/100 g FW).  Among the evaluated properties, iceberg lettuce showed favorable morphology, plant condition, and good dry matter content. In addition, between the loose-leaf lettuces, the red leaf lollo type was outstanding with bioactive content.